PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS, STRUKTUR KEPEMILIKAN KELUARGA TERHADAP TRANSFER PRICING PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2018-2020 - Fatoni Zulkarnaen; Agus Eko Sutriyono; Lia Nurina (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Ilmu Ekonomi (STIE) Pontianak, 2022)
This research aims to find out how influential the variables of company size, profitability, family ownership structure are on transfer pricing. This research using quantitative research is a study that emphasizes more on the aspect of objective measurement of transfer pricing. The sampling method used is nonprobability sampling, the overall sample used in this study is 75 annual financial report data from 25 companies. The analysis method used uses analsition regression of the research data. The results of this study show that company size, profitability, family ownership structure have a significant positive effect on transfer pricing. . Keywords: Company size, Profitability, Family Ownership Structure Towards Transfer Pricing.